ParticleAugment: Sampling-based data augmentation - Tsaregorodtsev, Alexander; Belagiannis, Vasileios (Computer Vision and Image Understanding, 2023)
We present an automated data augmentation approach for image classification. The problem is formulated as a Monte Carlo sampling problem where the goal is to approximate the optimal augmentation policies using a policy mixture distribution. We propose a particle filter scheme for the policy search where the probability of applying a set of augmentation operations forms the state of the filter. The policy performance is measured based on the loss function difference between a reference model and the actual model. This performance measure is then used to re-weight the particles and finally update the policy distribution. In our experiments, we show that our formulation for automated augmentation reaches promising results on CIFAR-10, CIFAR-100, and ImageNet datasets using the standard network architectures for this problem. By comparing with the related work, our method reaches a balance between the computational cost of policy search and the model performance. The source code of our approach is publicly available.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Automated augmentation; Deep learning optimization; Particle filters; Sequential Monte Carlo